2020
DOI: 10.1155/2020/8825189
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Washed Microbiota Transplantation on Helicobacter pylori Eradication: A Pilot Study

Abstract: Aim. The fecal microbiota transplantation by washed preparation was recently coined as washed microbiota transplantation (WMT). This pilot study is aimed at exploring the feasibility and efficacy of WMT on Helicobacter pylori eradication. Methods. Consecutive patients who had been treated with WMT for various indications and who were positive for H. pylori infection before WMT treatment but had never received eradication therapy for H. pylori infection were invited to take a follow-up 13C-urea breath test. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Washed preparation of FMT was applied in a recent pilot study to eradicate H. pylori infection. The result of this study indicated the potential capacity of FMT in attenuating H. pylori infection to some extent (Ye et al, 2020). Considering the substantial influence of FMT on the intestinal microbiota compared to the gastric microbiota, clinical trials have investigated the impact of FMT on lower gastrointestinal disorders including CRC (Chen et al, 2019).…”
Section: Beneficial Effects Of Fmt On H Pylori the Gut Microbiota And...mentioning
confidence: 89%
“…Washed preparation of FMT was applied in a recent pilot study to eradicate H. pylori infection. The result of this study indicated the potential capacity of FMT in attenuating H. pylori infection to some extent (Ye et al, 2020). Considering the substantial influence of FMT on the intestinal microbiota compared to the gastric microbiota, clinical trials have investigated the impact of FMT on lower gastrointestinal disorders including CRC (Chen et al, 2019).…”
Section: Beneficial Effects Of Fmt On H Pylori the Gut Microbiota And...mentioning
confidence: 89%
“…This public platform works hard to promote the transformation of WMT from clinical benefits to breakthrough in disease cognition. The latest pilot studies indicate the role of WMT on radiation colitis (Ding et al, 2020), complex infections (Dai et al, 2019), recurrent invasive fungal infection (Wu et al, 2021), refractory Helicobacter pylori infection (Ye et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…When compared to the adult population, repeated anesthesia, endoscopy, or enema, within short intervals, put children at greater risk; hence, we urgently need to explore a more convenient and safe delivery method. Colonic TET, as a new approach for colon-targeted drug delivery, was published for the first time in 2016 and has since been used in hospitals in China mainland [ 15 , 19 , 26 28 ] and China Taiwan since then [ 20 ]. In the present study, TET and WMT were successfully performed in all cases, and WMT or medicine retention time was longer than 1 hour.…”
Section: Discussionmentioning
confidence: 99%